Immunohistochemical localization of androgen receptors in female mole rat (Spalax leucodon) tissues - Gur, F. M.; Timurkaan, S. (Taylor & Francis Inc, 2016)
Androgens exert their effects through androgen receptors (AR) in tissues. We investigated the distribution of AR in female mole rat tissues. Tissues were excised, fixed with 10% formalin and embedded in paraffin. Sections were stained after microwave antigen retrieval for immunohistochemistry. Immunostaining of AR immunostaining was detected in the nucleus or cytoplasm of the cells in the cerebral cortex, cerebellum, anterior pituitary, lung, liver, uterus and skin. Granulosa and some thecal cells in the ovary, cardiac muscle cells and adipose cells exhibited a nuclear reaction for AR. In the kidney, labeling of AR was restricted to the cytoplasm of tubule cells. We found that AR could be detected using immunohistochemistry in the nucleus or cytoplasm or both in the presence of androgens.
Keywords: adipose tissue; androgen receptor; brain; cardiac muscle; female; immunohistochemistry; kidney; liver; lung; mole rats; ovary; pituitary; skin; uterus